Vimentin expression in benign and malignant breast epithelium. Issue 5 (May 1993) - Heatley, M; Whiteside, C; Maxwell, P; Toner, P
Abstract : AIMS--To determine vimentin expression in epithelial cells in benign breast disease and malignant breast tumours; to assess the value of vimentin expression as a prognostic indicator in breast carcinoma. METHODS--Frozen and formalin fixed, paraffin wax embedded sections from 78 carcinomas, three phyllodes tumours, 19 fibroadenomas and 19 cases of fibrocystic disease were examined with a monoclonal antibody from the V9 clone. A correlation between vimentin expression and known prognostic indicators was sought in ductal carcinomas. The intracellular localisation of vimentin was examined in benign and malignant lesions. RESULTS--Vimentin expression was identified on frozen section in the cells of ductal (53%), lobular (86%), and mucinous (33%) carcinomas and in the luminal epithelium of fibroadenomas (68%), cases of fibrocystic disease (47%), and a malignant phyllodes tumour. Formalin fixation reduced the percentage of carcinomas and cases of benign disease in which vimentin was detected. This reduction was more pronounced in fibroadenoma and fibrocystic disease than in ductal carcinoma. Associations were identified between vimentin expression as detected on frozen section and tumour grade, size, number of lymph nodes affected, oestrogen receptor content and growth fraction. Only the association with grade was significant (p = 0.045). There was no significant correlation between any of these prognostic variables and vimentin expression on paraffin wax sections. There was no difference in the intracellular localisation of vimentin staining between benign and malignant lesions, or between low and high grade ductal carcinomas. CONCLUSION--There is some loss of vimentin immunoreactivity after formalin fixation. Vimentin expression does not assist in differentiating between benign and malignant breast disease, but is correlated with tumour grade in ductal carcinoma.